Penerapan Jaringan Syaraf Tiruan dalam Memprediksi Tingkat Kriminal di Kabupaten Simalungun Menggunakan Algoritma Backpropagation - Muhammad Julham; S Sumarno; Fitri Anggraini; Anjar Wanto; S Solikhun (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2019)
The number of criminal rates that occur in the area of Simalungun Regency each year experiences an increase and decrease in crime cases each year. For example in the types of gambling crimes, in 2012 there were 89 cases, in 2013 there were 102 cases, in 2014 there were 92 cases, in 2015 there were 102 cases, in 2016 there were 94 cases, and in 2017 there were 86 cases. Then this problem is used as a basis in this study, which aims to provide information in the form of prediction data to the police in an effort to anticipate the rise in cases of types of crime in the following year. Efforts are being made to predict the level of crime in Simalungun Regency by applying the Bacpropagation algorithm ANN method. This research uses MATLAB R2011b and uses 5 architectural models to test the data that will be used for etimation / prediction, namely models 4-20-1, 4-30-1, 4-40-1, 4-50-1, 4- 70-1. Then the best architectural model results obtained are architectural models 4-20-1 with an accuracy of 93%, with the number of epochs 4575 in 51 seconds and MSE of 0,0009995011. This model will be used to predict Criminal Levels in Simalungun District from 2018 to 2022 with an accuracy of 93%.